A smart monitoring and controlling for agricultural pumps using LoRa IOT technology - Aktham Hasan Ali; Raad Farhood Chisab; Mohannad Jabbar Mnati (Institute of Advanced Engineering and Science, 2019)
Controlling electrical pumps on farms can be problematic, especially if there are a small number of people managing or working on huge areas of land and if the provision of electricity is not consistent. Therefore, further techniques for the management of plant irrigation on this type of land are being invented to make the process of irrigation easier. In this paper, a new intelligent device is designed and utilized to control the operation of irrigation pumps using a robust method of communication to transfer information at long distances, for the lowest cost, and the longest battery life. This technology is called LoRa (Long Range) communication, which is a low-power technology. The unit consists of two circuits: the first one is for switching the pumps ON and OFF, while the second one controls and monitoring the work of the pumps. Monitoring of the pumps can also be carried out through smart phones by measuring the voltage. The most important features of this new design are its intelligent control for long distances, cheap price, and a long operational life of more than five years. The goal of this paper is to help farmers by designing and manufacturing a remote-control system that switches irrigation pumps on and off using LoRa technologies.